Safety and Efficacy of Extracorporeal Photopheresis for Acute and Chronic Graft-versus-Host Disease - Eleni Gavriilaki; Eleni Papchianou; Giorgos Karavalakis; Ioannis Batsis; Alkistis Panteliadou; Andriana Lazaridou; Despina Mallouri; Varnavas Constantinou; Paraskevi Karvouni; Paschalis Evangelidis; Anna Papakonstantinou; Apostolia Papalexandri; et al. (MDPI AG, 2024)
Background/Objectives: Despite novel biological agents, steroid-dependent or -refractory graft-versus-host disease (GvHD) remains a severe complication of allogeneic hematopoietic cell transplantation (allo-HCT). Extracorporeal photopheresis (ECP) is an alternative, non-immunosuppressive treatment for patients with acute (aGvHD) or chronic (cGvHD) GvHD. The aim of this study was to investigate the safety and efficacy of ECP in the treatment of acute and chronic GvHD; Methods: We prospectively studied 112 patients with cGvHD who received one or more previous lines of treatment and 28 patients with steroid-dependent or refractory grade II-IV aGvHD post-alloHSCT. Results: In terms of severe aGvHD, most of the patients (19/28) responded to ECP treatment, while the five-year overall survival (OS) was 34%. After adjustment for several confounder factors, the reduction in immunosuppression (p = 0.026) and number of ECP sessions (p < 0.001) were associated with improved OS. Regarding chronic GvHD, only 19 patients failed to respond to ECP treatment; though significantly lower rates of response were presented in patients with visceral involvement (p = 0.037) and earlier post-transplant GVHD diagnosis (p = 0.001). Over a follow-up period of 45.2 [interquartile range (IQR): 5.6-345.1] months, the 5-year cumulative incidence (CI) of cGvHD-related mortality was 21.2% and was significantly reduced in patients with ECP response (p < 0.001), while the 5-year OS was 65.3%. Conclusions: Our results confirm the safety and efficacy of ECP in patients with GvHD and provide sufficient data for further investigation and the best combination drugs needed such that GvHD will not be the major barrier of allo-HCT in the near future.